Food habits of the Indian Wolf (Canis lupus pallipes) in Saurashtra, Gujarat, India - Ram, Mohan; Jhala, Lahar S.; Solanki, Divyesh P.; Parmar, Dilip; Mehta, Dhawal (Indian Forester, 2020)
Authors studied the food habits oflndian Wolfthrough scat analysis in three protected areas of the Saurashtra region of Gujarat namely Rampara Wildlife Sanctuary, Veiavadar Biackbuck National Park (and the adjoining Bhai region) and Jambudiya vidi during September-November 2017 and March-April 2019 respectively. The dietary composition varied in each of these areas. More than 95% scats consisted of a singie prey item. The wolves were dependent on livestock for over25% of their diet in Rampara and Jambudiya, whereas the diet ofwoives in VeiavadarBiackbuck National Park and Bhai region was comprised exclusively of wiid prey. The wild prey that dominated the diet included Biackbuck, Nilgai, Chinkara and Spotted Deer. Domestic livestock that was chiefly depredated included Goats and Cattle. The Indian Woifpopuiation in Saurashtra has greatly been reduced to small pockets and is subject to severe human-wildlife conflict and local extirpations which necessitates immediate conservation interventions. This study generates a baseline to devise future management strategies for the long term conservation of the Indian Woifin the Saurashtra region, one of the fewremaining bastions in the ever shrinking distribution range of the species.